Building a measure of digital citizenship values among social media users - Maryam Alqahtani (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aimed to build a measure of digital citizenship among users of social networking sites, and the society of the study consisted of (3.10) million active users within the country of Kuwait, including (29%) females and (71%) males. The sample of the study consisted of (12356) users of those who use social networking sites such as (Twitter, Instagram, Snapchat). The current study relied on the descriptive analytical method to reach the standard of digital citizenship, the scale included in its final form (56) items distributed on (6) dimensions digital etiquette, netiquette, digital access, digital rights, responsibilities, digital health & Wellness, digital commerce and digital security (self-protection). The study reached for the following results. First, the validity of the scale was verified in three ways: content validity (veracity of arbitrators), factor analysis, and internal consistency. Second, the reliability of the scale was verified in three ways: repeat method, half way, and internal consistency using the Cronbach Alpha equation. The results related to the performance standards of social media users showed that there were no differences in the levels of performance on the scale according to the gender.